PEMAHAMAN KONSEP EVALUASI DAN BENTUK EVALUASI DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Faatimatuzzahro; Lutfiyatus Sabrina; Salsabilah Fitri Riani; Nur Jihan Azka Afanti; Nirma Alimatulhana; Ely Mufidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning evaluation is a crucial instrument for measuring competency achievement and the success of internalizing historical values ​​in the Islamic Cultural History (ISCD) subject in Islamic Elementary Schools (Madrasah Ibtidaiyah). However, current evaluation practices tend to focus on cognitive aspects and do not yet reflect comprehensive assessments. This article aims to analyze the basic concept of learning evaluation and identify relevant types of evaluation in ISCD learning. This research uses a qualitative approach with a literature study method through the analysis of various books, scientific journals, and academic sources related to learning evaluation. The results of the study indicate that the concept of evaluation in ISCD learning is a systematic, continuous, and comprehensive process for assessing and making decisions regarding student learning outcomes, encompassing cognitive, affective, and psychomotor aspects. The types of evaluation used include diagnostic evaluation to determine initial abilities, formative evaluation to improve the learning process, and summative evaluation to measure final achievement. In addition, evaluation also plays a role in assessing changes in student attitudes and behavior in emulating the values ​​of Islamic figures. Thus, a comprehensive understanding of the concept and types of evaluation allows educators to develop assessment instruments that are more objective, holistic, and oriented towards developing student potential. This article also provides practical implications for educators in designing learning evaluations that are more comprehensive and oriented towards developing student character.